2018
DOI: 10.1126/science.aat3628
|View full text |Cite
|
Sign up to set email alerts
|

The prehistoric peopling of Southeast Asia

Abstract: The human occupation history of Southeast Asia (SEA) remains heavily debated. Current evidence suggests that SEA was occupied by Hòabìnhian hunter-gatherers until ~4000 years ago, when farming economies developed and expanded, restricting foraging groups to remote habitats. Some argue that agricultural development was indigenous; others favor the "two-layer" hypothesis that posits a southward expansion of farmers giving rise to present-day Southeast Asian genetic diversity. By sequencing 26 ancient human genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
423
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(459 citation statements)
references
References 89 publications
(10 reference statements)
30
423
3
3
Order By: Relevance
“…Another hypothesis suggests additional later southward expansion of EA populations. Current studies of SEA ancient human genomes indicated that both Hòabìnhian hunter‐gatherers first recognized about 44 ka years ago and southward expansion of EA farmers about 4,000 years ago influenced the diversity of present‐day SEA populations (Lipson et al, ; McColl et al, ). The findings agree with our ancestral population analyses that the present‐day SEA populations were mainly derived from the SEA ancestries and partly from the EA ancestries.…”
Section: Resultsmentioning
confidence: 99%
“…Another hypothesis suggests additional later southward expansion of EA populations. Current studies of SEA ancient human genomes indicated that both Hòabìnhian hunter‐gatherers first recognized about 44 ka years ago and southward expansion of EA farmers about 4,000 years ago influenced the diversity of present‐day SEA populations (Lipson et al, ; McColl et al, ). The findings agree with our ancestral population analyses that the present‐day SEA populations were mainly derived from the SEA ancestries and partly from the EA ancestries.…”
Section: Resultsmentioning
confidence: 99%
“…Hominin fossils in MSEA are restricted to heavily worn teeth or bone fragments, predominantly found in cave breccias or other sediments with uncertain depositional histories or equivocal chronologies. Recent fossil discoveries have pushed back the projected arrival of anatomically modern humans (AMH) in the region into Marine Isotope Stage (MIS) 4, 57 thousand years ago (ka) or earlier (Demeter et al, ; Rabett, ; Shackelford et al, ; Westaway et al, ), while morphological and genetic studies of fossil and modern populations hint at a complex history of interactions between diverse hominin species, including successive waves of modern humans (Bae, Douka, & Petraglia, ; Corny et al, ; Lipson et al, ; Liu et al, ; McColl et al, ; Sikora, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent fossil discoveries have pushed back the projected arrival of anatomically modern humans (AMH) in the region into Marine Isotope Stage (MIS) 4, 57 thousand years ago (ka) or earlier Rabett, 2018;Shackelford et al, 2018;Westaway et al, 2017), while morphological and genetic studies of fossil and modern populations hint at a complex history of interactions between diverse hominin species, including successive waves of modern humans (Bae, Douka, & Petraglia, 2017;Corny et al, 2017;Lipson et al, 2018;Liu et al, 2015;McColl et al, 2018;Sikora, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…A partial genome of a 3,000-years old Jomon individual from the east-north part of the main-island (Honshu) Japan was reported, but with very limited coverage (~ 0.03-fold) due to the poor preservation [14] . To identify the origin of the Jomon people, we sequenced a 1.85-fold genomic coverage of a 2,500-years old Jomon individual (IK002) excavated from the central part of the Japanese archipelago [15] . Comparing the Jomon whole-genome sequence with ancient Southeast Asians, we previously reported genetic affinity between IK002 and the 8,000-years old Hòabìnhian hunter-gatherer [15] .…”
Section: Introductionmentioning
confidence: 99%
“…To identify the origin of the Jomon people, we sequenced a 1.85-fold genomic coverage of a 2,500-years old Jomon individual (IK002) excavated from the central part of the Japanese archipelago [15] . Comparing the Jomon whole-genome sequence with ancient Southeast Asians, we previously reported genetic affinity between IK002 and the 8,000-years old Hòabìnhian hunter-gatherer [15] . This direct evidence on the link between the Jomon and Southeast Asians, thus, confirms the southern route origin of East Asians.…”
Section: Introductionmentioning
confidence: 99%